2017
DOI: 10.1038/s41598-017-02504-7
|View full text |Cite
|
Sign up to set email alerts
|

High visibility first-order subwavelength interference based on light pulse storage via electromagnetically induced transparency

Abstract: We achieved high visibility first-order subwavelength interference based on light pulse storage and retrieval technique via electromagnetically induced transparency (EIT) effect in a Pr3+:Y2SiO5 crystal. The interference field distribution of a double-slit was first stored in a Pr3+:Y2SiO5 crystal based on EIT effect, and then it was read out by a spatially modulated readout beam. The retrieved output field is proportional to the product of the input interference field of the double-slit and the spatially modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…We demonstrated that first-order subwavelength interference with high visibility through a spatial frequency doubling process can be achieved using the light pulse storage and retrieval technique based on the EIT effect in Pr:YSO crystal [103]. As shown in Figure 1, following an EIT-based light pulse storage and retrieval process, the retrieved signal pulse field, E S (x, y), can be written as…”
Section: First-order Subwavelength Interferencementioning
confidence: 99%
“…We demonstrated that first-order subwavelength interference with high visibility through a spatial frequency doubling process can be achieved using the light pulse storage and retrieval technique based on the EIT effect in Pr:YSO crystal [103]. As shown in Figure 1, following an EIT-based light pulse storage and retrieval process, the retrieved signal pulse field, E S (x, y), can be written as…”
Section: First-order Subwavelength Interferencementioning
confidence: 99%